Quantification of carotenoids in Korean fruits and vegetables using reverse-phase HPLC - Jung, Young-Jun; Ahn, Seung-Min; Lee, Hyungjae; Seo, Myung-Ji; Kim, Jae Kwang; Kim, Dae-Ok (Food science and biotechnology, 2025)
Carotenoids are natural pigments that have health benefits, including antioxidant capacities. The ability to assess the carotenoid content of fruits and vegetables is an essential element of nutritional and food science applications. We analyzed the contents of 10 major carotenoids (capsorubin, capsanthin, lutein, zeaxanthin, β-cryptoxanthin, [13 ]-β-carotene, α-carotene, β-carotene, [9 ]-β-carotene, and lycopene) in 30 types of fruits and 39 types of vegetables grown in Korea along with their associated processed products using reverse-phase HPLC. Carotenoids were generally more abundant in vegetables than in fruits. The most common carotenoid was β-carotene. Fruits were rich in β-cryptoxanthin, while vegetables were rich in lutein and β-carotene. Both capsorubin and capsanthin were found exclusively in red paprika, while capsanthin was also present in red sweet pepper. Lycopene was found only in grapefruit. These findings provide a comprehensive database of carotenoid contents in fruits and vegetables grown in Korea and can serve as a valuable resource for food science and processing. The online version contains supplementary material available at 10.1007/s10068-025-01861-8.